Effect of Reaction Time and Molar Ratio of Alcohol to Beef Tallow - Valentinoh Cuaca (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biodiesel is defined as renewable fuel for diesel engines, derived from vegetable oil or animal fats. Beef tallow is one residual material from slaughterhouses which main destination is the soap industry. The objective of the study was to utilize waste animal fat (beef) for biodiesel production using solid oxide catalyst. The solid oxide catalyst derived from the industrial waste shells of egg. The waste materials calcined in air with temperature 900 oC and time 2 hours, transformed calcium species in the shells into active CaO catalysts. The oil contains high free fatty acid (FFA) content of 1.85%. The acid value of the oil was reduced by acid esterification. The product from this stage was subjected to transesterification to produce biodiesel. Transesterification process produces methyl ester and glycerol. The produced methyl ester on the upper layer was separated from the glycerol and then washed. Effect of various process variables such as reaction time and molar ratio of alcohol to beef tallow were investigated. The biodiesel properties like methyl ester content, density, and viscosity was evaluated and was found to compare well with Indonesian Standard (SNI). Under best condition, the maximum yield of 82,43% beef tallow methyl ester was obtained by using 9:1 molar ratio of methanol to beef tallow at 55 oC, for a reaction time 90 minutes in the presence 3 wt% of CaO catalyst. The results of this work showed that the use of beef tallow is very suitable as low cost feedstock for biodiesel production.